Faunistic Composition Of Frugivorous Butterflies (Lepidoptera: Nymphalidae) In Lowland Dipterocarp Forest At Kubah National Park, Kuching, Sarawak - Liew, Sze Tze (Universiti Malaysia Sarawak (UNIMAS), 2014)
Butterflies are important in the work of conservation since they are the most appropriate model for habitat monitoring and rapid assessment on biodiversity. The exact information on the effect of habitat disturbance on the biodiversity within the tropical rainforest is still lacking and associated with difficulties in predicting them. This study was coniucted to test the hypothesis that there was a presence of frugivorous nymphalids that have specific niche. "The vertical stratification of frugivorous nymphalids in lowland dipterocarp forest was also being examined in this study. The faunistic composition of frugivorous nymphalids was studied by using ten baited traps in which five baited traps were set for canopy and another five baited traps were set for understory, for 15 days. The baited traps for canopy and understory were set on a selected tree at 20m and 1 m above the ground respectively. Ripe pineapples and mashed bananas were used as the bait. The baited traps were left to function from 0800 hours to 1700 hours. Forty one individuals of frugivorous nymphalids, comprised of three subfamilies and eight species were captured in this study, including 3 rare species: Mycalesis maianeas kadaan, Bassarona dunya monara and Neorina lowii lowii. The most abundant species was Ragadia makuta umbrata, whereas the least abundant species was Amathxidia amythaon ottomana. The faunistic composition of frugivorous nymphalids in lowland dipterocarp forest was different with other forest types, indicating some of them are good indicators. Conservation should also be carried out to protect those rare forest butterflie;.